The Anthelmintic Activity of Ethanol Extract of Bitter Leaf (Vernonia amygdalina) Against Ascaridia galli Worm in Vitro - Amelia Dwita Safitri; Iwan Sahrial Hamid; Poedji Hastutiek; Setiawan Koesdarto; Rahmi Sugihartuti; Endang Suprihati (Journal of Parasite Science (JoPS), 2019)
The aims of this study is to know the anthelmintic activity of ethanol extract of bitter leaf (Vernonia amygdalina) against Ascaridia galli worm in Vitro, as well as knowing effective concentration 50 (EC50) and lethal time 50 (LT50). Method that used in the research was completely randomized design. There were five treatments of physiological NaCl solution (K-), piperazine sitrate (K+), etanol extract of bitter leaf 0,35% (P1), etanol extract of bitter leaf 1,4% (P2), etanol extract of bitter leaf 4,2% (P3), and each treatment was done in four replications. This research used ten Ascaridia galli in each treatment for all replications. The observation and recording of dead Ascaridia galli was done at 2, 4, 6, 8, 10 and 12 hours. Ascaridia galli were declared dead if there was no movement when disturbed by anatomy tweezer and when dipped in slightly warm water (50°C). The obtained data was analyzed using ANAVA and continued with Duncan Multiple Range Test. The result of this research show that etanol extract of bitter leaf (Vernonia amygdalina) has anthelmintic effects against Ascaridia galli worm in Vitro. In the extract with 4,2% concentration, there is anthelmintic property that almost the same as Piperazine sitrate 10 mg/ml. the higher the concentration of extract, the higher the property of anthelmintic. In probit analysis show that EC50 achieved by concentration 2.093% with the low concentration of .002% and the highest concentration of 3.632%. LT50 of ethanol extract of bitter leaf was 0.35% at 10.323 hours, 1.4% at 9.800 hours, 4.2% at 7.864 hours and Piperazine sitrate 10 mg/ml at 9.013 hours.